Neural effects of mindfulness-based interventions on patients with major depressive disorder: A systematic review. (May 2018) - Vignaud, Philippe; Donde, Clément; Sadki, Thouraya; Poulet, Emmanuel; Brunelin, Jérôme
Highlights: The prefrontal cortex, cingulate cortex, and basal ganglia are modified after MBI in depression. Attentional processes and self-awareness are key aspects of the effects of MBI on depression. The MBI-induced neural changes are correlated with clinical improvements. Abstract: Growing evidence has suggested that mindfulness-based interventions (MBIs) could have beneficial effects on the acute phase of depression and on the prevention of depressive relapse or recurrence. Despite growing clinical interest, the effects of MBIs on brain functioning in patients with MDD remain unclear. The aim of this systematic review was to assess the changes in brain functioning associated with MBIs in patients with MDD. A systematic search was conducted, and of the 56 articles found, 8 were eligible. MBIs have modulatory effects on several brain regions implicated in the pathophysiology of MDD, such as the prefrontal cortex, the basal ganglia, the anterior and posterior cingulate cortices, and the parietal cortex. These regions have been implicated in self-awareness, attention and emotion regulation. Some of these findings were consistent with the effects of MBIs observed in healthy subjects and patients with other psychiatric disorders, especially enhanced activity in the frontal and subcortical regions related to the improved somatosensory awareness. Further studies are needed to elucidate the mechanisms of MBIs in MDD.